INTERACTIVE DATA VISUALIZATION AND ANALYTICS FOR SENSOR AND BIOIMAGE DATA IN AGING RESEARCH. (11th November 2018) - Zhu, H; Tsai, T; Poole, V N; Manor, B; Dufour, A B; Isaza Aizpurua, I I; Travison, T G
Abstract: Clinical aging research often utilizes data from external media sources such as accelerometer sensor data and bioimages. A customary research workflow makes use of this information by extracting quantitative values, which may be summaries, using simplification algorithms. This treatment, while efficient, risks loss of information and reduction of resolution and fidelity of the resulting data. We have thus developed customizable web-based tools to pair raw data from external sources with other clinical data, and to visualize and analyze them together without preprocessing. We have integrated these visualization tools into customizable study monitoring dashboards that can be accessed from the internet, are accessible to quantitative and clinical scientists, and which can be interactively manipulated to perform data processing, analyses, or even the development of clinical assessments at the participant level. We demonstrate the performance of this approach using movement sensor data from a smartphone study, and dynamic participant-level bioimages by MRI.